1) sin a = √2/2; a1 = pi/4+2pi*k; cos a1 = √2/2 a2 = 3pi/4+2pi*k; cos a2 = -√2/2 cos(60 + a1) = cos 60*cos a1 - sin 60*sin a1 = = 1/2*√2/2 - √3/2*√2/2 = √2/4*(1 - √3) = -√2(√3 - 1)/4 cos(60 + a2) = cos 60*cos a2 - sin 60*sin a2 = = -1/2*√2/2 - √3/2*√2/2 = -√2/4*(1 + √3) = -√2(√3 + 1)/4
2) sin a = 2/3; cos b = -3/4; a ∈ (pi/2; pi); b ∈ (pi; 3pi/2) cos a < 0; sin^2 a = 4/9; cos^2 a = 1-4/9 = 5/9; cos a = -√5/3 sin b < 0; cos^2 b = 9/16; sin^2 b = 1-9/16 = 7/16; sin b = -√7/4 sin(a+b) = sin a*cos b + cos a*sin b = = 2/3*(-3/4) + (-√5/3)(-√7/4) = -6/12 + √35/12 = (√35 - 6)/12 cos(-b) = cos b = -3/4
1y-0.5-0.5+0.2y+1=0
1.2y=0
y=0
ответ: 0
2) (x² +3x+2)(x² +3x+4)=8
(x² +3x+2)(x² +3x+2+2)=8
y=x² +3x+2
y(y+2)=8
y² +2y-8=0
D=4+32=36
y₁=(-2-6)/2= -4
y₂=(-2+6)/2=2
При у= -4
x² +3x+2= -4
x² +3x+2+4=0
x² +3x+6=0
D=9-24<0
нет решений.
При у=2
x² +3x+2=2
x² +3x+2-2=0
x² +3x=0
x(x+3)=0
x=0 x+3=0
x= -3
ответ: -3; 0.
3) (x² -2x-3)(4-x² +2x)= -2
(x² -2x-3)*(-(x² -2x-4))= -2
(x² -2x-3)(x² -2x-3-1)=2
y=x² -2x-3
y(y-1)=2
y² -y-2=0
D=1+8=9
y₁=(1-3)/2= -1
y₂=(1+3)/2=2
При у= -1
x² -2x-3= -1
x² -2x-3+1=0
x² -2x-2=0
D=4+8=12
x₁=(2-√12)/2=(2-2√3)/2=1-√3
x₂=1+√3
ответ: 1-√3; 1+√3
4) (x² -x-11)(x² -x-21)= -9
(x² -x-11)(x² -x-11-10)= -9
y=x² -x-11
y(y-10)= -9
y² -10y+9=0
D=100-36=64
y₁=(10-8)/2=1
y₂=(10+8)/2=9
При у=1
x² -x-11=1
x² -x-11-1=0
x² -x-12=0
D=1+48=49
x₁=(1-7)/2= -3
x₂=(1+7)/2=4
При у=9
x² -x-11=9
x² -x-11-9=0
x² -x-20=0
D=1+80=81
x₁=(1-9)/2= -4
x₂=(1+9)/2=5
ответ: -4; -3; 4; 5.